PREDICTORS OF MORTALITY AMONG COVID-19 PATIENTS IN LUBUMBASHI, DEMOCRATIC REPUBLIC OF CONGO - Gerald Ardito (Journal of E-Learning and Educational Technologies (JEET), 2023)
The ongoing pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has claimed millions of lives worldwide. This retrospective cohort study aimed to identify predictors of mortality and evaluate survival among COVID-19 patients in Lubumbashi, Democratic Republic of Congo, from July to September 2021. The study collected data from hospitals in Lubumbashi that take care of COVID-19 patients. The sample consisted of 1276 patients, with 684 males and 592 females. The study found that age above 40, male gender, and diabetes were potential predictors of mortality for COVID-19 patients in Lubumbashi. The survival rate decreased by 20% within 20 days of admission, with the survival rate decreasing to 5% for patients below 40 years of age, 15% for those aged 40-59, and 23% for those aged 60 or above. Male patients had a lower survival rate of 20%, while female patients had a survival rate of approximately 15%. Patients with diabetes had a lower survival rate of approximately 15%. Comorbidities such as hypertension, diabetes, stroke, and respiratory diseases decreased the survival rate among COVID-19 patients. The study highlights the importance of early detection, adequate treatment, and management of comorbidities to improve the survival rate of COVID-19 patients in Lubumbashi.